Propuesta de un plan de mejora al sistema de seguridad y salud del trabajo en el área de pulpado de concentrado de tomate de la empresa de conserva de vegetales “la conchita”. - Logro Tumbaco, Diego Armando (2012)
The following investigative work was carried out in the area of Concentrated Tomato in the Company of Preserves of Vegetables "La Conchita." It took as general objective of the investigation: to elaborate a proposal for the improvement of the System of Security and Health of the Work in the Area of Concentrated Tomato. The following specific objectives were traced: to analyze studies of norms and resolutions of the Security and Health of the Work in the area, to diagnose the current conditions of the industrial security and the main labor risks and to propose solutions to minimize the risks labor and the detected problems of security. The principal conclusions were: Most of the risks identified in the area are severe causing that the work atmosphere is insecure. The faulty administration of the Security and Health in the Work in the area study object are due to organizational problems. The application of the action plan proposed to the detected problems and of the Manual of Security for the area will allow minimizing the risks to perfect the System of Security and Health of the Work of the company.